2012
DOI: 10.1001/archinternmed.2011.677
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Iodinated Contrast Media Exposure and Incident Hyperthyroidism and Hypothyroidism

Abstract: Iodinated contrast media exposure is associated with subsequent development of incident hyperthyroidism and incident overt hypothyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
147
0
15

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(163 citation statements)
references
References 50 publications
1
147
0
15
Order By: Relevance
“…Recognition in this highly competitive protic media has predominantly been the domain of highly charged hydrogen‐bonding receptors, which are frequently pH‐dependent3 or metal‐cation‐based systems;46 although some recent progress has been made in exploiting the hydrophobic effect for anion recognition by neutral host species 7–10. Amongst the plethora of biologically and medically relevant anions, the recognition and sensing of iodide in water is of interest both due to its crucial role in hormone biosynthesis by the thyroid gland11, 12 and its use in contrast media for radiographic imaging applications 13. Examples of anion hosts capable of sensing iodide by optical methods are scarce,1417 and to the best of our knowledge, the use of molecular‐anion receptors for the host–guest recognition and sensing of iodide in water is unprecedented.…”
Section: Introductionmentioning
confidence: 99%
“…Recognition in this highly competitive protic media has predominantly been the domain of highly charged hydrogen‐bonding receptors, which are frequently pH‐dependent3 or metal‐cation‐based systems;46 although some recent progress has been made in exploiting the hydrophobic effect for anion recognition by neutral host species 7–10. Amongst the plethora of biologically and medically relevant anions, the recognition and sensing of iodide in water is of interest both due to its crucial role in hormone biosynthesis by the thyroid gland11, 12 and its use in contrast media for radiographic imaging applications 13. Examples of anion hosts capable of sensing iodide by optical methods are scarce,1417 and to the best of our knowledge, the use of molecular‐anion receptors for the host–guest recognition and sensing of iodide in water is unprecedented.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced age, large thyroid volume, multinodular goiter and thyroid autonomy make the risk group in development of iodine-related thyrotoxicosis (27). The history of nontoxic diffuse or nodular goiter that occurs most frequently in the areas of iodine deficiency could not be well ascertained in Rhee et al (22), although this is the most commonly reported risk factor for iodine-induced hyperthyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The iodine-containing contrast media for imaging purposes such as coronary angiography (CA), is widespread use result in considerable iodine load of the thyroid gland, which is mainly caused by in vivo deiodination of the contrast medium (17,18). Several studies have reported thyroid dysfunction following administration of contrast agent (16,(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained data through the Partners Healthcare Research Patient Data Registry, a central clinical data warehouse for .1.8 million inpatients and outpatients designed for research and quality improvement (23)(24)(25). Approval for this study was granted by the Institutional Review Board at Brigham and Women's Hospital and the need for informed consent was waived.…”
Section: Data Collectionmentioning
confidence: 99%